Oral contraceptive use in women changes preferences for male facial masculinity and is associated with partner facial masculinity - Little, Anthony C.; Burriss, Robert P.; Petrie, Marion; Jones, Benedict C.; Roberts, S. Craig (Psychoneuroendocrinology, 2013)
Millions of women use hormonal contraception and it has been suggested that such use may alter mate preferences. To examine the impact of oral contraceptive (pill) use on preferences, we tested for within-subject changes in preferences for masculine faces in women initiating pill use. Between two sessions, initiation of pill use significantly decreased women's preferences for male facial masculinity but did not influence preferences for same-sex faces. To test whether altered preference during pill use influences actual partner choice, we examined facial characteristics in 170 age-matched male partners of women who reported having either been using or not using the pill when the partnership was formed. Both facial measurements and perceptual judgements demonstrated that partners of women who used the pill during mate choice have less masculine faces than partners of women who did not use hormonal contraception at this time. Our data (A) provide the first experimental evidence that initiation of pill use in women causes changes in facial preferences and (B) documents downstream effects of these changes on real-life partner selection. Given that hormonal contraceptive use is widespread, effects of pill use on the processes of partner formation have important implications for relationship stability and may have other biologically relevant consequences.